High-resolution reconstruction of paleoclimate during the last 72 ka on the basis of the drilled sediments from Lake Nojiri, central Japan - 公文, 富士夫; 河合, 小百合; 井内, 美郎
長野県北部の野尻湖で掘削された堆積物試料に対して､花粉分析と有機炭素分析に基づいて7.2万年前から現在までの古気候を復元した｡ 7.2万年前から6.2万年前(MIS 4)の時代はゴヨウマツ類やトウヒ属を主とする亜寒帯針葉樹林が卓越する寒冷な気候であった｡ 6.2万年前から2.9万年前(MIS 3)までは相対的に落葉広葉樹の比率が高く､冷涼な気候であったが､数百年から2､ 3千年周期の短い寒暖変動が多数認められる｡この中では5.5-4.5万年前が相対的に最温暖の時期であり､その後2.9万年前に向かって寒冷化が進行する｡ ATテフラはその最末期に位置する｡ 2.9万年前から1.8万年前(MIS 2前半)にかけてはトウヒ属やモミ属を主とする亜寒帯針葉樹林が卓越しており､厳しい寒さの時期(最終氷期最寒冷期)であった｡ 1.8万年前からコナラ亜属の増加に示される温暖化が始まり､何度かの寒の戻りを経ながら､ 1.4万年前から1.2万年前にかけて急激に温暖化する｡この1.8- 1.2万年前が晩氷期にあたる｡ 1.2万年前以降(MIS 1)では､冷温帯落葉広葉樹が卓越する温暖な気候が継続するが､多少の寒暖変動も認められる｡ Paleoclimate during the last 72 ka has been reconstructed in detail, based on the pollen and total organic carbon analyses on the drilled sediment core from Lake Nojiri, central Japan. The climate from 72 to 62 ka (MIS 4) was cold and dry with predominance of Pinus (Hapoxylon) and Picea. During 62 to 29 ka (MIS 3), deciduous broad-leaved trees were dominant, indicating a relatively warm period. AT tephra marks well the end of this term. Relatively warmest timing is around 55 to 45 ka, and quasi-periodic repeats of abrupt warming and cooling identified may correspond with the Dansgaard-Oeschger cycle. The climate in 29 to 18 ka (early MIS2) was coldest, the Last Glacial Maximum, and was characterized by dominance of subarctic conifers such as Picea and Ables. A slight warming started around 18 ka, followed by some cooling phases. This is the deglaciation time of the Last Glacial age (late MIS2). It became warm to the present level abruptly at 12 ka, and stable warm climate have continued during the last 12 ka (MIS 1), associated with a small fluctuations. Article 旧石器研究. 5:3-10 (2009) journal article